Gendered Citizenship in Italian Administrative Law: A Work in Progress Toward a New Public Ethics. (2nd January 2016) - Simonati, Anna
Abstract : The involvement of people of both genders in public life is connected with improvements in the quality of administrative action because it brings about greater pluralism of ideas and sensitivity to equal opportunities. The transposition into public law of the idea of gendered citizenship would be useful as an ideal foundation for rules regarding equal treatment of men and women. Specific aspects of existing legal instruments in Italy are analyzed, along with the implications of current best practices. This analysis of the elements that compose the legal paradigm of gender citizenship offers relevant outcomes for the future action of legislators and policymakers, in Europe and around the globe.